ANEMIA DAN DEFISIENSI BESI PADA SISWA SLTP NEGERI I CURUG, TANGERANG - Fify Henrika; T. Silangit; Riadi Wirawan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
A research was conducted to 69 female students from a junior high school (SLtP) Negeri I Curug, tangerang aged 12–14 yearsto obtain percentages of anemia and iron deficiency in female adolescents. Anemia was found on 10.2% of the students, with 4.3%of normocytic normochromic anemia and 5.8% of microcytic hypochromic anemia. Microcytic hypochromic erythrocytes was foundon 21.7% of the subjects which consist of 2.9% iron deficiency anemia, 1.4% phase 2 iron deficiency (latent) with possibility ofhemoglobinopathy, and 2.9% phase 1 iron deficiency (pre-latent) with possibility of hemoglobinopathy. Anemia without iron deficiencywith possibility of chronic diseases and/or hemoglobinopathy was 2.9%, and without anemia nor iron deficiency but with possibility ofhemoglobinopathy was 11.6%. Iron deficiency was found among 26.1% of subjects which consist of 11.6% pre-latent iron deficiency,8.7% latent iron deficiency, and 5.8% iron deficiency anemia with 2.9% and 2.9% were normocytic normochromic anemia andmicrocytic hypochromic anemia, respectively.